Antenatal steroids: a caveat to the applause? Long term impact of antenatal glucocorticoid exposure on aortic structure and function: a 20 year prospective follow-up study of premature infants. (7th June 2011) - Kelly, B; Lazdam, M; Lewandowski, A; Lucas, A; Trevitt, C; Kylintireas, I; Worton, S; Leeson, P
Abstract : Background: A course of glucocorticoids (GCs), betamethasone or dexamethasone, is advised for pregnant women at risk of preterm delivery. Transient GC-exposure in animals during fetal life has lasting effects on vascular function, renewing concern that antenatal GCs may influence early life programming of cardiovascular risk.1 Changes in blood pressure are not a universal finding in young adults exposed to antenatal steroids.2 However, cuff sphygmomanometry, is insufficiently sensitive to assess cardiovascular risk in young and otherwise asymptomatic adults.3 Aim: To comprehensively phenotype cardiovascular structure and function in antenatal steroid-exposed/non-exposed preterm offspring at aged 25–28 years. Methods: A 20-year prospective follow–up study of a well-defined preterm cohort born 1982–1985, integrating MRI of central arterial structure/function to assess aortic pulse wave velocity (PWV) and aortic distensibility, with global vascular PWV and wave reflection measured by tonometry and endothelial function by flow-mediated dilation (FMD) and assessment of metabolic profile. Results: 13 GC-exposed (GC-E) and 63 non-GC-exposed (Cont) adults were studied. Gestational age and birthweight were similar between groups (GC-E: 29±1.7; cont:30.5±2.6; 1239 g±316 vs 1310 g ±274). Ascending aortic distensibility was reduced (GC-E:9.4 (SD3.2)mm Hg; Cont: 12.7 (SD 3.7)mm Hg; p=0.02) and aortic arch PWV increased (GC-E: 7.5 (SD1.36)ms-1; Cont: 5.6 (SD1.4)ms-1; p=0.03) in GC-exposed adults (adjusted for gender, BMI, smoking). There were no significant differences in metabolic profile (lipids/HOMA/fasting glucose), peripheral/central pulse pressures, global arterial stiffness or endothelial function. Conclusion: These findings suggest a selective GC effect on ascending aortic structure/function in preterm-born young adults exposed to antenatal steroids, indicating possible increased future cardiovascular risk.